Pendampingan Partisipatif Untuk Penguatan Kapasitas Manajerial Dan Digitalisasi UMKM Di Kelurahan Mencirim Binjai Timur - Isnan Sarwo Prasetyo; Yoni Adelia (Sevaka : Hasil Kegiatan Layanan Masyarakat, 2026)
This community service initiative aims to enhance the managerial capacity and digitalization skills of MSME owners in Mencirim Village, East Binjai. Initial observations revealed five structural issues: weak financial record-keeping, conventional marketing strategies, minimal use of social media for promotion, lack of brand identity, and limited understanding of pricing strategy. The methodology employed a Participatory Action Approach (PAA), encompassing needs identification, structured training, practical workshops, and six weeks of intensive mentoring for 25 MSME participants. Results indicate a substantial increase across all measured indicators: 84% of participants implemented simple bookkeeping, 76% actively used social media for promotion, 72% developed brand identities, and 80% demonstrated improved pricing strategies all surpassing the established targets. Wilcoxon Signed-Rank Test confirmed statistical significance (p < 0.05). The program also fostered entrepreneurial mindset shifts, the formation of local business networks, and the emergence of community-based local leaders. Continuous mentoring and cross-stakeholder collaboration are recommended to sustain long-term economic impact.